Highlights from the 1st Latin American meeting on metronomic chemotherapy and drug repositioning in oncology, 27–28 May, 2016, Rosario, Argentina - Rose, Adriana (2016)
Following previous metronomic meetings in Marseille (2011), Milano (2014), and Mumbai (2016), the first Latin American metronomic meeting was held in the School of Medical Sciences, National University of Rosario, Rosario, Argentina on 27 and 28 of May, 2016. For the first time, clinicians and researchers with experience in the field of metronomics, coming from different countries in Latin America, had the opportunity of presenting and discussing their work. The talks were organised in three main sessions related to experience in the pre-clinical, and clinical (paediatric and adult) areas. The different presentations demonstrated that the fields of metronomic chemotherapy and repurposing drugs in oncology, known as metronomics, constitute a branch of cancer therapy in permanent evolution, which have strong groups working in LatinAmerica, both in the preclinical and the clinical settings including large, adequately designed randomised studies. It was shown that metronomics offers treatments, which, whether they are combined or not with the standard therapeutic approaches, are not only effective but also minimally toxic, with the consequent improvement of the patient’s quality of life, and inexpensive, a feature very important in low resource clinical settings. The potential use of metronomic chemotherapy was proposed as a cost/effective treatment in low-/middle-income countries, for adjuvant therapy in selected tumours. The fundamental role of the governmental agencies and non-governmental alliances, as the Metronomic Global Health Initiative, in supporting this research with public interest was underlined.